A COMPREHENSIVE ANALYSIS OF MAHARASHTRA'S SOCIAL WELFARE PROGRAMS - Goel, Neha; Kurup, Manoj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Independence came with both visible and invisible costs. The Indian economy was crawling post-partition. India’s economic stature can be seen through its share of the world’s GDP which resulted in a stupendous increase in population, and a higher percentage of the population in poverty, which created a massive inequality in society. These inequalities become hindrances for society, further widening the gap between rich and poor. .This article is a sincere attempt to examine the social welfare programs implemented by the federal and state governments, with a focus on the state of Maharashtra, and how they have helped those in need. and investigating a few facets of migrant assistance programs. It examines every state revenue division and evaluates its success using metrics including GDP contribution, literacy, sex ratio, and HDI.